The Determinants of the Treasury Security Yield Curve - ROLEY, V. VANCE (Journal of Finance, 1981)
ABSTRACT Investors' security demands and two points on the yield curve are jointly determined using a disaggregated structural model of the U.S. Treasury securities market. The empirical results indicate that the structural model is capable of accurately explaining Treasury yields and that changes in a variety of nonyield variables affect the yield curve. Among these nonyield variables are Treasury security supplies, which are found to have significant but somewhat volatile impacts depending on investors' wealth flows. The within‐sample predictions from the structural model are also compared to those of a naive model.